The microbial metabolite trimethylamine N-oxide and the kidney diseases - Su, Jin-Qi; Wu, Xiang-Qi; Wang, Qi; Xie, Bo-Yang; Xiao, Cui-Yan; Su, Hong-Yong; Tang, Ji-Xin; Yao, Cui-Wei (Frontiers in Cellular and Infection Microbiology, 2025)
Trimethylamine N-oxide (TMAO), a metabolite, is a co-metabolite produced by both gut microbiota and livers, originating from foods rich in choline or carnitine. Emerging evidence suggests that TMAO may play a role in the pathogenesis of various kidney diseases, including acute kidney injury and chronic kidney disease. Research has demonstrated that heightened levels of TMAO are correlated with a heightened likelihood of kidney disease advancement and cardiovascular incidents among individuals with chronic kidney disease. Furthermore, TMAO has been observed to stimulate inflammation, oxidative stress, and fibrosis in animal models of kidney disease. Mechanistically, TMAO may contribute to kidney disease pathogenesis by inhibiting autophagy, activating the NLRP3 inflammasome, and inducing mitochondrial dysfunction. Therefore, targeting TMAO may represent a promising therapeutic strategy for the treatment of kidney diseases. Future studies are needed to further investigate the role of TMAO in kidney disease pathogenesis and to develop TMAO-targeted therapies for the prevention and treatment of kidney diseases.